Frequency of Incorrect Challenged Medicolegal Certificates: Multicentre Experience in Interior of Sindh - Ghulam Sarwar Pirzada, Kanwal Kumar, Rashid Ahmed Pathan, Saeed Ahmed Shaikh, Afzal Memon. Ghulam Kadir Kaheri , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2013)
Objective: To determine the rate ofincorrect medico legal certificates. Design: Descriptive, Observational. Place: Departments of Forensic Medicine, People University ofMedical & Health Sciences for Women Nawabshah (Shaheed Benazirabad), Ghulam Mohammad Mahar Medical College Sukkur and Chandka Medical College, Shaheed Mohtarrna Benazir Bhutto Medical University, Larkana. Duration: August 2012 to March 2013. Material and Methods: A total 307 medico-legal certificates were challenged from various districts of interior of Sindh in the special medical boards. The information from the certificate regarding person's age, gender, site of injury/scar and the area victim belongs was entered in a standard proforma designed for this purpose, and analyzed on SPSS version 16. Results: Of 307 cases, 102 ( 33.22%) were incorrect with highest number due to fabrication & almost four times more in male than female. The highest involvement age group was in 21-40 years. In majority of cases injuries/scars were on head & face 69.61% and more in persons belonging to rural areas 84.31%. Conclusion: About 1/3'd certificates are incorrect issued by Medico-legal officers, more in a male of young age group belongs to rural areas.